1991
DOI: 10.3109/00365529108996495
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Autonomic Nerve Function in Patients with Crohn's Disease

Abstract: Autonomic nerve function was evaluated in 33 patients with Crohn's disease (age range, 19-66 years; mean, 36 years) by three established non-invasive tests based on the heart reactions to deep breathing (E/I ratio) and to tilt (acceleration and brake indices). Peripheral nerve function was evaluated neurographically and by measuring thresholds to vibration and temperature changes. None of the patients were diabetic, and all had normal thyroid function. In spite of normal peripheral nerve function, almost half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 24 publications
5
63
2
2
Order By: Relevance
“…Ohlsson et al reported a patient with subclinical sympathetic neuropathy which appears early in the course of CD. In contrast to prior reports but in accordance to the study of Gondim, autonomic evaluation of our patients did not disclose any abnormality [10,31]. The actual pathogenesis inciting the peripheral neuropathy in patients with CD is uncertain.…”
Section: Polyneuropathy In Crohn Diseasecontrasting
confidence: 56%
See 1 more Smart Citation
“…Ohlsson et al reported a patient with subclinical sympathetic neuropathy which appears early in the course of CD. In contrast to prior reports but in accordance to the study of Gondim, autonomic evaluation of our patients did not disclose any abnormality [10,31]. The actual pathogenesis inciting the peripheral neuropathy in patients with CD is uncertain.…”
Section: Polyneuropathy In Crohn Diseasecontrasting
confidence: 56%
“…At a later stage of the disease a primarily mononeuritis multiplex or asymmetric polyneuropathy could evolve towards a symmetrical picture by summation of multifocal lesions [17]. Boylu et al reported a patient with CD and chronic inflammatory demyelinating polyneuropa- [31]. The occurrence of AN was not related to the duration or severity of CD or to biochemical evidence of inflammation or malabsorption of vitamins and trace elements.…”
Section: Polyneuropathy In Crohn Diseasementioning
confidence: 99%
“…Patients from the Departments of Surgery and Medicine at the University Hospital of Malmö suffering from CD and UC, previously examined by autonomic nerve (AN) function tests (11,12) were evaluated. All patients who had undergone surgical resections were included in the present study.…”
Section: Subjectsmentioning
confidence: 99%
“…However, EGCs have not yet been demonstrated as autoimmune targets. Studies aimed at examining potential EGC autoantigens, antigen presentation, and their relative contribution in inducing the neuropathy that is common in Crohn's disease patients are therefore warranted (Dvorak and Silen, 1985;Lindgren et al, 1991;Elsehety and Bertorini, 1997).…”
Section: Potential Mechanisms For Enteric Glial Cell Ablation and Dysmentioning
confidence: 99%